Influences on MSME Sustainability: The roles of financial literacy, business capital, and financial inclusion - Komang Sri Widiantari; I Gede Krisna Sedana Putra; Ida Nyoman Basmantra (Review of Management, Accounting, and Business Studies, 2024)
This study investigated the influence of financial literacy and business capital on the sustainability of Micro, Small, and Medium Enterprises (MSMEs) in Denpasar, Indonesia, considering financial inclusion as a moderating variable. MSMEs in Indonesia contribute significantly to economic growth but often face sustainability challenges due to limited financial knowledge and capital access. Using a quantitative approach, data were collected from 100 MSME operators in Denpasar via a structured questionnaire. The study employed Partial Least Squares (PLS) for data analysis, with descriptive statistics to provide insights into demographic characteristics and variable distributions. Results revealed that business capital had a significant and positive impact on MSME sustainability, while financial literacy showed no substantial direct effect. Additionally, financial inclusion did not significantly moderate the relationship between financial literacy, business capital, and sustainability outcomes. This finding suggested that MSMEs require more tailored financial products and advisory services to meet their specific operational needs rather than broad access to financial services alone. The study’s results offer insights for policymakers and financial institutions, emphasizing the importance of customized financial support to foster MSME sustainability in a competitive environment.